2017
DOI: 10.1007/s11999-016-4812-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher Frequency of Reoperation With a New Bicruciate-retaining Total Knee Arthroplasty

Abstract: Background With as many as 25% of patients reporting residual knee symptoms after primary total knee arthroplasty (TKA), alternative implant designs and surgical techniques have been proposed to further reduce these symptoms. There is growing evidence that retention of the anterior cruciate ligament (ACL) results in more natural knee kinematics; thus, implants with more normal joint mechanics could provide improved physical function postoperatively and reduce the amount of residual symptoms. Advancements in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 30 publications
4
47
0
Order By: Relevance
“…Similar findings were noted by Pritchett, who reported a 23 year survivorship of 89% in 489 BCR TKAs, with only four revisions of the femoral and tibial components [6]. In contrast, Christensen et al reported higher frequency of revision and increased radiolucent lines under the tibial tray for BCR compared to a conventional cruciate-retaining TKA [41]. However, as noted by the study's authors, the mean follow-up time was short (1.29 years), the sample size was small (n = 66), and initial learning curve experience could have influenced the results.…”
Section: Discussionsupporting
confidence: 73%
“…Similar findings were noted by Pritchett, who reported a 23 year survivorship of 89% in 489 BCR TKAs, with only four revisions of the femoral and tibial components [6]. In contrast, Christensen et al reported higher frequency of revision and increased radiolucent lines under the tibial tray for BCR compared to a conventional cruciate-retaining TKA [41]. However, as noted by the study's authors, the mean follow-up time was short (1.29 years), the sample size was small (n = 66), and initial learning curve experience could have influenced the results.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, reduced medial condyle lowest point posterior translation and notable opposing internal rotation motion trends in BCR TKA during most of the stance phase were found when compared to the data reported for PS TK . In a recent study comparing the same BCR TKA design used in our study against CR TKA, Christensen et al reported longer mean surgical durations for BCR TKA and a higher frequency of all‐cause revision, reoperation and radiolucent lines at a mean of 18 months. In addition, there were no differences in patient reported clinical outcomes between the BCR and CR TKA groups.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, a previous study reported that the BCR implant has inferior survivorship and concerning radiographic findings when compared with a conventional cruciate retaining (CR) implant with respect to complications after primary TKA. 10 However, there were no differences in patient-reported clinical outcomes (PROM) between the BCR and CR TKA groups. Component misalignment has been suggested as one important factor associated with accelerated wear, poor functional outcomes, and increased revision rates in contemporary TKA designs, 11,12 thus precise component alignment may be important for the optimization of patient reported clinical outcomes in BCR TKA.…”
mentioning
confidence: 90%